2017
DOI: 10.15761/crt.1000170
|View full text |Cite
|
Sign up to set email alerts
|

Bronchiolitis in adult: A review

Abstract: Few diseases have a greater effect on the health of young children than viral respiratory illness of lower tract. This does not happen in adults, possibly due to the different states of activation and expression of the innate immune response and acquired immune responses in these two age groups. Bronchiolitis is a general term used to describe non-specific inflammatory injury that primarily affects the small airways and generally limits the extent to interstice. In the adult clinic, conventional and high-resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…Common causes of acute bronchiolitis include infection, aspiration, toxic inhalation such as smoking, and connective tissue diseases. 9 A retrospective study of patients hospitalized with lower respiratory tract infection characterized by diffuse acute bronchiolitis revealed that the most common infectious etiologies were M. pneumoniae, influenza virus, H. influenzae, respiratory syncytial virus, rhinovirus, and S. pneumoniae. 10 Various causes of acute bronchiolitis may have similar pathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Common causes of acute bronchiolitis include infection, aspiration, toxic inhalation such as smoking, and connective tissue diseases. 9 A retrospective study of patients hospitalized with lower respiratory tract infection characterized by diffuse acute bronchiolitis revealed that the most common infectious etiologies were M. pneumoniae, influenza virus, H. influenzae, respiratory syncytial virus, rhinovirus, and S. pneumoniae. 10 Various causes of acute bronchiolitis may have similar pathological findings.…”
Section: Discussionmentioning
confidence: 99%
“…The involvement of small airways (<2 mm internal diameter and without cartilage) due to obliterative bronchiolitis is an important factor in countries with endemic tuberculosis [34]. In a series of obliterative bronchiolitis, 98% of the causes were infectious and within these, 78% were post-tuberculosis [24].…”
Section: Air Flow Obstruction Mechanism and Pulmonary Function In Topdmentioning
confidence: 99%